Critics on Policy of Soy-Based Infant Formula in Indonesia: Compared to Australian and New Zealand Food Standards - Agnescia Clarissa Sera (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: World Health Organization (WHO) recommends breast milk as sole and the most complete infant food during the first 6 months. However, in certain circumstances, when breastfeeding is not possible, not desired or not advised, infant formulas like those are made of soy can be given to newborns. However, the safety of long-term use soy-based formula has been argued due to the possible adverse effects of phytoestrogen, phytates and aluminum in human body as well as the consequences of agrochemicals residue. Therefore, those problems should be taken into account while developing, reviewing or amending policy of infant formulas. This article reviews the adequacy of soy-based infant formula policy in Indonesia to anticipate issues in SIF consumption. Methods: Australian and New Zealand Food Standards Code was used to compared to the decree of Indonesian NADFC. The results were described narratively and analyzed from the perspective of the author. Results: Accordingly, only small aspects of SIF are regulated in Indonesian policy. The use of SPI for SIF in Indonesia is not a compulsory though scientifically another source may trigger diarrhea in newborn baby. No clause related to aluminum content, zinc to copper ratio, isoflavone level, GM soy and pesticide residue found in Indonesian policy. Conclusion: Apparently, very limited provision regarding SIF has been covered by Indonesian policy. The regulation of SIF marketed and manufactured in Indonesia should be more specific and developed based on recent clinical and epidemiological studies. On the other hand, Indonesia needs a comprehensive system where society may participate in reviewing the laws. Keywords: soy-based infant formula, food policy, food standards Received: 14 May 2019 Reviewed: 18 June 2019 Revised: 1 July 2019 Accepted: 6 July 2019 DOI: 10.35898/ghmj-33588